Is cultural activity at work related to mental health in employees? - Theorell, Töres (Springer-Verlag, 2012)
OBJECTIVE: To examine relationships between work-based cultural activities and mental employee health in working Swedes. HYPOTHESIS: A positive relationship between frequent cultural activity at work and good employee health was expected. RESEARCH DESIGN: Random sample of working Swedish men and women in three waves, 2006, 2008 and 2010, on average 60 % participation rate. METHODS: A postal questionnaire with questions about cultural activities organised for employees and about emotional exhaustion (Maslach) and depressive symptoms (short form of SCL). Employee assessments of “non-listening manager” and work environment (“psychological demands” and “decision latitude”) as well as socioeconomic variables were covariates. Cross-sectional analyses for each study year as well as prospective analyses for 2006–2008 and 2008–2010 were performed. MAIN OUTCOME AND RESULTS: Lower frequency of cultural activities at work during the period of high unemployment. The effects of relationships with emotional exhaustion were more significant than those with depressive symptoms. The associations were attenuated when adjustments were made for manager function (does your manager listen?) and demand/control. Associations were more pronounced during the period with low unemployment and high cultural activity at work (2008). In a prospective analysis, cultural activity at work in 2008 had an independent statistically significant “protective” effect on emotional exhaustion in 2010. No corresponding such association was found between 2006 and 2008. CONCLUSIONS: Cultural activities at work vary according to business cycle and have a statistical association with mental employee health, particularly with emotional exhaustion. IMPLICATIONS FOR FUTURE RESEARCH: There are particularly pronounced statistical protective effects of frequent cultural activity at work on likelihood of emotional exhaustion among employees.